Storing and Retrieving Information in the framework of the Phonemic Spectrum Theory (Raparin Journal of Humanities (RJH), 2021)
This research is entitled (storing and retrieving information in the framework of the phonemic spectrum theory), and its analysis focuses on the perception mechanism and the production and representation of speech sounds within the internal components of the mind. It means producing sounds, storing them and then retrieving them from mental memories. The level of phonology, but these sounds within their wavelengths are converted into white light compounds and connections, in terms of the surface feature, but in terms of their verbal features they are hidden and retain features that distinguish them from others. This research is divided into two main sections:     The first section is devoted to the introduction of the theory of the night and the history of the uprising, and the definition of each of the sounds, speech, and language according to this theory. The second section deals with how to store and retrieving sounds. also in the second section the phonemic features are discussed, as a basis for the separation of the sounds.in concludes with representing most important results and laying out the references.